YIIFSWA II OPENDAY - Food Testing - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2019)
Testing of foods made from yam to access the quality. YIIFSWA-II showcases High Ratio Propagation Technologies and demonstrates large scale production of early generation seed yam at the project's open day in 2018.